Preparation of Land Resources Development Plan by Implementing AHP-based Weighted Overlay Analysis on Geospatial Inputs - Pathak, Suparn; Arora, Virat; Rao, S S; Raj, Uday (Annals of Arid Zone, 2019)
Planning for sustainable development of land resources demands suggestion for best alternate land-use based on the prevailing geo-environment. This practice is assisted by geospatial analysis that involves evaluation of multiple inputs such as existing land cover, ground water prospects, land capability, geomorphology and slope. Judgement on the basis of relative importance among the input layers is highly subjective which significantly affects the results. This study uses a mathematical method named Analytical Hierarchy Process (AHP) for assigning weights to the input layers while performing weight-based overlay analysis for preparing Land Resources Development Plan (LRDP) of a development Block in arid western plain zone of India. A pair-wise comparison matrix was prepared illustrating the importance of each of the layers with respect to other. Normalized principal eigenvectors generated from this matrix were used as weights in further analysis. The input layers were rescaled on the scale of 1 to 10 considering their favorability towards alternate land-uses like intensive agriculture, agro-horticulture, agro-forestry, silvi-pasture, fodder and fuel wood. Favorability maps were generated for each alternate land-use by applying AHP-derived weights. An integrated output (LRDP) was produced by allocating label to every location depicting name of the alternate land-use that scored best among all the favorability scores at that location. LRDP thus prepared is a cost effective method for planners to combat land degradation incorporating different opinions of experts regarding the weightage of input theme layers.Key words: Sustainable land use planning, land resources development plan (LRDP), geographic information system (GIS), weighted overlay analysis, analytic hierarchy process (AHP).